2010
DOI: 10.1057/jors.2009.150
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the applicability of system dynamics to patient flow modelling

Abstract: The objective of this research is to determine whether Systems Dynamics (SD) is a beneficial method for modelling hospital patient flow from a strategic planning perspective. While discrete event simulation has frequently been used as a tool for analysing and improving patient flow in health care settings, the desire to assess and understand patient flow and resource demand from a more strategic, and therefore aggregate, perspective led to the use of SD. To evaluate the suitability of such an approach, a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…This might be compared to a study of health care where, by and large, both the medical provider and patient aspects are either well documented or can be monitored. This observation, and the preceding discussion exemplify why the extensive literature on modelling, for example, the health system, including discrete-event simulation (DES) leading to systems dynamics-based optimisation (Vanderby and Carter 2010;Smits 2010;Davies et al 2000;Fone et al 2003;Robinson 2005) is not applicable to this case.…”
Section: Information Availabilitymentioning
confidence: 95%
“…This might be compared to a study of health care where, by and large, both the medical provider and patient aspects are either well documented or can be monitored. This observation, and the preceding discussion exemplify why the extensive literature on modelling, for example, the health system, including discrete-event simulation (DES) leading to systems dynamics-based optimisation (Vanderby and Carter 2010;Smits 2010;Davies et al 2000;Fone et al 2003;Robinson 2005) is not applicable to this case.…”
Section: Information Availabilitymentioning
confidence: 95%
“…Simulation is by far the most common methodological tool used in support of these types of studies [17][18][19]. Coté [20] used discrete event simulation (SIMAN IV) at an outpatient clinic to describe and quantify issues related to patient flow and resource utilization for an individual physician.…”
Section: Simulationmentioning
confidence: 99%
“…They found that the maximum number of patients that could be served was linearly related to the number of procedure rooms, with a fixed room-toendoscopist ratio, and that changes in the patient arrival schedule could reduce patient waiting time without requiring a longer clinic day. For other applications of discrete event simulation in healthcare, see, e.g., [23,24]; for similar applications using system dynamics, see, e.g., [19,25].…”
Section: Simulationmentioning
confidence: 99%
“…The quantitative SD approach to simulation is viable where the model can be validated against a real--world foundation of data and measurable relationships or processes. Several recent examples of quantitative and qualitative applications in specific healthcare domains are available in the literature (Vanderby and Carter 2009;Wong et al 2012). This paper describes a whole--systems SD approach to modelling and evaluation of healthcare sustainability, at the macro level of a public healthcare system.…”
mentioning
confidence: 99%